Enhancing Hearing Protection: Evaluating Innovative Training Modalities for Optimal Fitting Outcomes - Samelli, Alessandra Giannella; Maia Rabelo, Camila; Alves Martins, Daiane; Akina Shinya, Indra; Martins Guesser, Vitor; Rocha, Clayton Henrique (La Medicina del Lavoro, 2025)
Background: Measuring the effectiveness of training in properly fitting hearing protection devices (HPDs) is crucial, as it directly influences their attenuation. We assessed an earplug’s personal attenuation ratings (PAR) following various intervention modalities. Methods: The sample consisted of 52 adults without experience using hearing protection devices (HPD). The Personal Attenuation Rating (PAR) was evaluated through real-ear attenuation at threshold (REAT) and microphone-in real-ear (MIRE) measurements after participants fitted the HPD as they saw fit. Participants were then randomly assigned to groups and given instructions on HPD fitting as follows: (G1) individual in-person demonstration; (G2) package reading; (G3) video; (G4) no intervention. PAR was subsequently reassessed. Data analysis was conducted using ANOVA and the Fisher Exact test. Results: Pre-intervention assessments showed no significant differences between the groups using either method. After training, G1, G2, and G3 significantly increased the PAR compared to G4, through both processes. The comparison of PAR post and pre-intervention revealed significant differences for G1, G2, and G3 (REAT) as well as for G1 and G3 (MIRE), in contrast to G4. Regarding “pass” and “fail” outcomes through MIRE, G1, G2, and G3 had more “pass” results after the intervention, compared to G4. Conclusions: Intervention, regardless of modality, effectively improved correct earplug HPD fitting, evidenced by increased PAR and higher rates of individuals achieving sufficient attenuation. Individual in-person demonstrations and video instructions proved to be the most effective training modalities.